NEW EVIDENCE ON NATIONAL BOARD CERTIFICATION AS A SIGNAL OF TEACHER QUALITY. (27th November 2017) - Horoi, Irina; Bhai, Moiz
Abstract : Using longitudinal data from North Carolina that contains detailed identifiers, we estimate the effect of having a National Board for Professional Teaching Standards (NBPTS) teacher on academic achievement. We identify the effects of an NBPTS teacher exploiting multiple sources of variation including traditional‐lagged achievement models, twin‐ and sibling‐fixed effects, and aggregate grade‐level variation. Our preferred estimates show that students taught by National Board certified teachers have higher math and reading scores by 0.04 and 0.01 of a standard deviation. We find that an NBPTS math teacher increases the present value of students' lifetime income by $48, 000. ( JEL I20, I21, J2444)